Legal mechanisms for protecting social and labor rights of citizens The study is funded by the Scientific Committee of the Ministry of Education and Science of the Republic of Kazakhstan (No. AP09259109 grant)) (Journal of actual problems of jurisprudence, 2023)
In the modern world, issues of social protection of the population and social and labor rights of citizens are relevant for many countries. In this regard, various studies and analyses are conducted aimed at identifying problems and finding ways to solve them. Social and labor rights of citizens are of great importance for society as a whole and for each individual. They provide equal opportunities in the labor sphere, protection from discrimination and social protection in difficult economic conditions. Protection of social and labor rights of citizens is an urgent task in modern society. This is due to the fact that social and labor rights are the main guarantees of social protection and ensuring equality between citizens, including in the field of labor.Social and labor rights include the right to work, the right to protection from discrimination, the right to social insurance, the right to rest and leisure, the right to equal pay for work and others. They are an integral part of human rights, and their protection guarantees respect for human dignity and social justice.However, despite the fact that social and labor rights are protected by legislation and international conventions, the implementation of these rights is not always ensured in practice. Employers may violate the rights of employees, for example, by not paying wages on time, violating safety and labor standards, discriminating against employees on various grounds, etc. In addition, some categories of workers may be deprived of social insurance and other guarantees.Therefore, the protection of social and labor rights of citizens remains an urgent task. This requires not only improving legislation and its effective implementation, but also raising awareness of citizens about their rights and obligations, as well as improving the skills of law enforcement agencies and other specialists engaged in the protection of social and labor rights. In addition, it is important to promote the principles of social responsibility in the sphere of business and the public in order to ensure fair and equal working conditions for all citizens.Therefore, it is necessary to constantly improve legislation in this area and ensure its effective implementation.Keywords: the right to work, the right to protection from discrimination, the right to social insurance, the right to rest and leisure, the right to equal pay for work.